Crystallization of Supercooled Liquids: Self-Consistency Correction of the Steady-State Nucleation Rate - Alexander S. Abyzov; Jürn W. P. Schmelzer; Vladimir M. Fokin; Edgar D. Zanotto (Entropy, 2020)
Crystal nucleation can be described by a set of kinetic equations that appropriately account for both the thermodynamic and kinetic factors governing this process. The mathematical analysis of this set of equations allows one to formulate analytical expressions for the basic characteristics of nucleation, i.e., the steady-state nucleation rate and the steady-state cluster-size distribution. These two quantities depend on the work of formation, <semantics> Δ G ( n ) = − n Δ μ + γ n 2 / 3 </semantics> , of crystal clusters of size n and, in particular, on the work of critical cluster formation, <semantics> Δ G ( n c ) </semantics> . The first term in the expression for <semantics> Δ G ( n ) </semantics> describes changes in the bulk contributions (expressed by the chemical potential difference, <semantics> Δ μ </semantics> ) to the Gibbs free energy caused by cluster formation, whereas the second one reflects surface contributions (expressed by the surface tension, <semantics> σ </semantics> : <semantics> γ = Ω <msubsup> d 0 2 </msubsup> σ </semantics> , <semantics> Ω = 4 π ( 3 / 4 π ) 2 / 3 </semantics> , where <semantics> d 0 </semantics> is a parameter describing the size of the particles in the liquid undergoing crystallization), n is the number of particles (atoms or molecules) in a crystallite, and <semantics> n = n c </semantics> defines the size of the critical crystallite, corresponding to the maximum (in general, a saddle point) of the Gibbs free energy, G. The work of cluster formation is commonly identified with the difference between the Gibbs free energy of a system containing a cluster with n particles and the homogeneous initial state. For the formation of a “cluster” of size <semantics> n = 1 </semantics> , no work is required. However, the commonly used relation for <semantics> Δ G ( n ) </semantics> given above leads to a finite value for <semantics> n = 1 </semantics> . By this reason, for a correct determination of the work of cluster formation, a self-consistency correction should be introduced employing instead of <semantics> Δ G ( n ) </semantics> an expression of the form <semantics> Δ <mover accent="true"> G ˜ </mover> ( n ) = Δ G ( n ) − Δ G ( 1 ) </semantics> . Such self-consistency correction is usually omitted assuming that the inequality <semantics> Δ G ( n ) ≫ Δ G ( 1 ) </semantics> holds. In the present paper, we show that: (i) This inequality is frequently not fulfilled in crystal nucleation processes. (ii) The form and the results of the numerical solution of the set of kinetic equations are not affected by self-consistency corrections. However, (iii) the predictions of the analytical relations for the steady-state nucleation rate and the steady-state cluster-size distribution differ considerably in dependence of whether such correction is introduced or not. In particular, neglecting the self-consistency correction overestimates the work of critical cluster formation and leads, consequently, to far too low theoretical values for the steady-state nucleation rates. For the system studied here as a typical example (lithium disilicate, <semantics> Li 2 O · 2 SiO 2 </semantics> ), the resulting deviations from the correct values may reach 20 orders of magnitude. Consequently, neglecting self-consistency corrections may result in severe errors in the interpretation of experimental data if, as it is usually done, the analytical relations for the steady-state nucleation rate or the steady-state cluster-size distribution are employed for their determination.